DIFERENCIAÇÃO CLÍNICA DA BRONCOPNEUMONIA MODERADA E GRAVE EM BEZERROS - Gonçalves, Roberto Calderon [UNESP]; Kuchembuck, Márcio Rubens Graf [UNESP]; Curi, Paulo Roberto [UNESP]; Chiacchio, Simone Biagio [UNESP]; Almeida, Clóvis Teixeira De [UNESP]; Borges, Alexandre Secorun [UNESP] (Universidade Federal de Santa Maria, 2001)
To evaluate the main clinical signs of bronchopneumonia in calves and determie the classification as moderate or severe form, 48 calves were divided in 3 groups: 10 clinically healthy animals (G1), 18 animals with moderate bronchopneumonia (G2) and 20 animals with severe bronchopneumonia (G3). The classification of these experimental groups was based on clinical characterization and confirmed by statistical Group Analysis. In the clinically healthy calves (G1), the results revealed absence of clinical signs of respiratory disease and low clinical score. The calves with bronchopneumonia were identified by the association of clinical signs showing pulmonary abnormalities. Cough and positive cough reflex, high corporal temperature and cardiac rate, abnormal tracheobronchial and bronchobronchiolar noises and interrupted inspiration were important in the bronchopneumonia diagnosis but did not differentiated the severe or moderate cases. High respiratory rate, dispnoea, signs of compact parenchyma, silence areas and crackles and whizzels were the most important signs to differentiate the clinical cases of bronchopneumonia.

Com o objetivo de identificar os principais sinais clínicos de bezerros com broncopneumonia e definir a doença nas formas moderada e grave, foram utilizados 48 bezerros divididos em 3 grupos: 10 clinicamente sadios (G1), 18 com broncopneumonia moderada (G2) e 20 com broncopneumonia grave (G3). A classificação dos grupos sadios e doentes (broncopneumonia moderada e grave) obedeceu a critérios clínicos e foi confirmada estatisticamente por Análise de Agrupamento. Os resultados evidenciaram ausência de sinais clínicos compatíveis com doença respiratória e menor escore clínico nos bezerros clinicamente sadios (G1). Os bezerros com broncopneumonia foram identificados pela presença de diversos sinais clínicos, confirmando anormalidades pulmonares. Tosse e reflexo de tosse positivo, aumento de temperatura e freqüência cardíaca, alterações dos ruídos traqueobrônquico e broncobronquiolar e inspiração interrompida, apesar de relacionados ao diagnóstico de broncopneumonia, não diferenciaram a intensidade moderada e grave do processo. A freqüência respiratória elevada, a dispnéia mista, a submacicez/macicez, área de silêncio, a crepitação grossa e os roncos e sibilos definiram a gravidade do quadro de broncopneumonia.
CLINICAL DIFFERENTIATION OF MODERATE AND SEVERE BRONCHOPNEUMONIA IN CALVES
Keywords: bronchopneumonia; calves; clinical signs; respiratory sounds; broncopneumonia; bezerros; sinais clínicos; sons respiratórios